Smoking Cessation Behavior in Children: What is the Role of Parents and Peers? - Abdus Salam; Rif'ah, Erwin; Rokhmah, Dewi (Universitas Airlangga, 2023)
Background: Pangarengan District is one of the areas in Sampang Regency with a fairly high number of child smokers, namely the age of 14 years as much as 26.6% and 11 years old as much as 15.4%, among elementary schools as much as 24.3%. Aims: The purpose of this study was to analyze the form of social support from parents and peers on smoking behavior in children in Pangarengan District, Sampang Regency. Method: This research is qualitative research with a phenomenological approach. There are 15 informants consisting of 5 main informants and 10 additional informants. Determination of informants used a purposive technique. Data collection techniques in this study were in-depth interviews, observation, and documentation. Data analysis used thematic content analysis. Credibility tests used source triangulation and technical triangulation. Results: Based on the results of the study, all informants received emotional support in the form of smoking bans, attention, care, and advice. Informants get instrumental support in the form of suggestions, input, and appeals to reduce cigarette consumption. In addition, the informants received support in the form of positive enthusiasm and encouragement to stop smoking, as well as gifts promised by their parents. Informants also received information support about the dangers of smoking and diseases made worse by smoking. Conclusion: The conclusion of this study is that all informants have received social support from their parents and peer groups. This study is expected to change smoking behavior in children by reducing cigarette consumption.